Electrical Imaging of Light-Induced Signals Across and Within Retinal Layers - Lee, Meng-Jung; Zeck, Günther (Frontiers in Neuroscience, 2020)
The mammalian retina processes sensory signals through two major pathways: a vertical excitatory pathway, which involves photoreceptors, bipolar cells and ganglion cells, and a horizontal inhibitory pathway, which involves horizontal cells and amacrine cells. This concept explains the generation of excitatory center – inhibitory surround sensory receptive fields but fails to explain modulation of the retinal output by stimuli outside the receptive field. Electrical imaging of the light-induced signal propagation at high spatial and temporal resolution across and within different retinal layers might reveal mechanisms and circuits involved in the remote modulation of the retinal output. Here we took advantage of a high-density CMOS-based microelectrode array and investigated light-induced propagation of local field potentials (LFPs) in vertical mouse retina slices. Surprisingly, the LFPs propagation within the different retinal layers depends on stimulus duration and stimulus background. Application of the same spatially restricted light stimuli to flat-mount retina induced ganglion cell activity at remote distances from stimulus center. This effect disappeared if a global background was provided or if gap junctions were blocked. We hereby present a neurotechnological approach and demonstrated its application, in which electrical imaging evaluates stimulus-dependent signal processing across different neural layers.